2022
DOI: 10.3389/fpls.2022.837231
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the Potato Monosaccharide Transporter StSWEET7a Promotes Root Colonization by Symbiotic and Pathogenic Fungi by Increasing Root Sink Strength

Abstract: Root colonization by filamentous fungi modifies sugar partitioning in plants by increasing the sink strength. As a result, a transcriptional reprogramming of sugar transporters takes place. Here we have further advanced in the characterization of the potato SWEET sugar transporters and their regulation in response to the colonization by symbiotic and pathogenic fungi. We previously showed that root colonization by the AM fungus Rhizophagus irregularis induces a major transcriptional reprogramming of the 35 pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 92 publications
1
10
0
Order By: Relevance
“…In addition, it has been reported that the constitutive overexpression of StSWEET7a , a Glc and fructose transporter from potato, induces accumulation of StInvCD141 transcripts in non‐mycorrhizal roots and increases the frequency and abundance of mycorrhizal colonization when plants are inoculated with R. irregularis (Tamayo et al, 2022). It was proposed that the overexpression of StSWEET7a depletes the apoplast from monosaccharides, and consequently, the sink strength is increased by the upregulation of cell wall‐bound invertases to promote the unloading of Suc to the apoplast (Tamayo et al, 2022). In tomato, Suc depletion in the periarbuscular space mediated by the SUT2 transporter has been reported as a mechanism to control the supply of C to the AMF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it has been reported that the constitutive overexpression of StSWEET7a , a Glc and fructose transporter from potato, induces accumulation of StInvCD141 transcripts in non‐mycorrhizal roots and increases the frequency and abundance of mycorrhizal colonization when plants are inoculated with R. irregularis (Tamayo et al, 2022). It was proposed that the overexpression of StSWEET7a depletes the apoplast from monosaccharides, and consequently, the sink strength is increased by the upregulation of cell wall‐bound invertases to promote the unloading of Suc to the apoplast (Tamayo et al, 2022). In tomato, Suc depletion in the periarbuscular space mediated by the SUT2 transporter has been reported as a mechanism to control the supply of C to the AMF.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that the upregulation of a cell wall‐bound invertase gene in potato occurs in parallel with the upregulation of genes coding for SWEET, which are responsible for the mobilization of Suc and monosaccharides (Manck‐Götzenberger & Requena, 2016). In addition, it has been reported that the constitutive overexpression of StSWEET7a , a Glc and fructose transporter from potato, induces accumulation of StInvCD141 transcripts in non‐mycorrhizal roots and increases the frequency and abundance of mycorrhizal colonization when plants are inoculated with R. irregularis (Tamayo et al, 2022). It was proposed that the overexpression of StSWEET7a depletes the apoplast from monosaccharides, and consequently, the sink strength is increased by the upregulation of cell wall‐bound invertases to promote the unloading of Suc to the apoplast (Tamayo et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 17 ] Moreover, ectopic expression of plasma membrane‐localized SWEET7a increased glucose secretion from roots in potato plants as indicated by increased cell wall invertase levels and arbuscular mycorrhiza colonization. [ 18 ]…”
Section: Introductionmentioning
confidence: 99%
“…[17] Moreover, ectopic expression of plasma membranelocalized SWEET7a increased glucose secretion from roots in potato plants as indicated by increased cell wall invertase levels and arbuscular mycorrhiza colonization. [18] Increased carbon sink strength, resulting from increased sugar storage, consumption, or secretion, can reduce growth when it cannot be balanced by increased source strength, that is, higher photosynthesis rates. Under non-stressed conditions, plants like Arabidopsis and potato were shown to compensate for increased sugar consumption in sink tissues by increased photosynthesis rates.…”
Section: Introductionmentioning
confidence: 99%